Substitution of murine transthyretin (prealbumin) regulatory sequences into the Moloney murine leukemia virus long terminal repeat yields infectious virus with altered biological properties. - Feuer, G (1990)
The effects of inserting cellular regulatory sequences from the murine transthyretin (TTR) gene into the Moloney murine leukemia virus (M-MuLV) long terminal repeat (LTR) were investigated. Transthyretin is expressed predominantly in the liver and choroid plexus in adult mice, and TTR upstream regulatory elements were previously shown to potentiate transcription in liver-derived cells. The effects of inserting the TTR distal enhancer and/or promoter-proximal sequences into an M-MuLV LTR lacking its enhancers were measured in three ways. (i) Chimeric LTRs were fused to the bacterial chloramphenicol acetyltransferase gene (cat) and tested for transient gene expression by transfection into liver-derived cells or NIH 3T3 fibroblasts. (ii) Infectious M-MuLV containing an altered LTR [delta Mo + TTR(PD) MuLV) was generated, and infectivity in culture on hepatocyte lines and NIH 3T3 cells was tested. (iii) Infection of delta Mo + TTR(PD) MuLV in vivo was tested by inoculating NFS/N mice and performing in situ hybridization of whole animal sections. Chimeric LTR-cat constructs showed higher levels of cat gene expression in liver-derived cell lines than in NIH 3T3 cells, indicating increased LTR activity in these cells. However, in vitro infection did not show significantly higher infectivity in hepatocytes for delta Mo + TTR(PD) M-MuLV than did wild-type M-MuLV. In vivo, delta Mo + TTR(PD) MuLV showed expression in the same tissues as with wild-type M-MuLV-inoculated mice, i.e., lymphoid organs and the intestines and, additionally, two novel sites not seen in wild-type M-MuLV-inoculated animals. Of 10 mice, 8 showed viral expression in the brain and 3 showed expression in the liver. Thus, insertion of TTR elements into the M-MuLV LTR altered LTR activity both in vitro and in vivo.